Intercropping and farmer income: a case study of onion farmers in Tawangmangu - Agung Prasetyo; Mahananto; Suswadi; Kusriani Prasetyowati; Norbertus Citra Irawan; Eko Hartoyo; Nadian Nur Aulia (JURNAL ILMIAH AGRINECA, 2022)
Onion farmers in Tawangmangu are currently experiencing difficulties due to changes in rainfall. As a result, they are planting garlic and then intercropping with shallots. This decision will have a direct impact on farmers' income. This study aims to determine the effect of farmers' decisions in intercropping garlic with shallots on farmers' income in the Tawangmangu District. This research was conducted in Tawangmangu District with a simple random sampling method to determine the sample size of 49 respondents. The method of data analysis used a two-stage least square. The decision to intercrop shallot and garlic does not affect farmers' income. The age of the farmer influences the decision to do intercropping. A farmer's income is influenced by land area and the use of Phonska fertilizer. To increase farmers' income, using fertilizers with similar elements must be paid more attention to when fertilizing plants.